SOSIALISASI PANDUAN KLASIFIKASI DAN KONSTRUKSI KAPAL IKAN FRP KURANG DARI 12 METER DI WILAYAH PESISIR PULAU RAAM - Nurul Huda; Andreas Pujianto; Yani Nurita Purnawanti; Boby Wisely Ziliwu; Rezza Ruzuqi; Ahmad Nurfauzi; Djoko Prasetyo; Bagas Prakoso; Muhfizar Muhfizar; Egbert Joshua Sirait; Pundi Ramadhan Sudrajat (Politeknik Kelautan dan Perikanan Sorong, 2022)
Raam Island is a village located in the city of Sorong, West Papua Province which has several business groups for FRP boat craftsmen, especially for fishing purposes. The standard manufacturing process standards applied by fiber ship craftsmen make the quality of the fabrication results different from each existing shipyard. The socialization activity was carried out by presenting materials directly to shipyard owners and FRP ship craftsmen. BKI as a state-owned company engaged in survey services and ship certification has regulations related to ship construction. In 2020, BKI issued